PEMBELAJARAN INQUIRY MENGGUNAKAN GOOGLE FORM TERHADAP HASIL BELAJAR SIMULASI DAN KOMUNIKASI DIGITAL - Popi Radyuli; Rini Sefriani Sefriani; Nurul Qomariah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2019)
This study aims to determine whether there is influence of Inquiry learning model using Google Form on the learning outcomes of class X digital communication and simulation subjects based on research conducted at SMK Negeri 9 Padang, Jl. Bundo Kanduang No. 18 West Padang class X Culinary department in odd semester 2018/2019 academic year, obtained the final average value in the experimental class given learning with the Inquiry model of 88.78 and the control class given learning using the conventional method of 77.19. The test results t_count ^ = 8.5221, for ttable ^ = 2.338 so that it is obtained t_count ^> t table ^ (8.5221> 2.338. Thus H0 is rejected and H1 is accepted, which means that there is a positive effect of applying Inquiry learning models using Google Form against learning outcomes of class X digital simulation and communication subjects at SMK Negeri 9 Padang in the odd semester of the 2018/2019 academic year.